Soužití ruské menšiny s domácími národnostmi v pobaltských státech - Rauscherová, Kristina (Univerzita Karlova, Pedagogická fakulta, 2007)
Key words: Lithuania, Latvia, Estonia, Baltic countries, Russians, national minorities This graduation these explains and analyses the current position of Russian national minority in the Baltic states, especially in Latvia and Estonia. It analyses their co-existence in terms of political, legal and socio-economic aspects as well as in terms of researches, which were conducted in this field. All of the researches, which the work extracts from, were focused on the evaluation of the mutual relations by Russians and the native population. The feeling of Russian minority concerning their current identity was also taken into account. The aim of this work is to define the model of co-existence of the Russian minority and the major population and indicate the development of this co-existence in the future. Práce přibližuje a analyzuje současné postavení ruské národnostní menšiny v pobaltských státech s důrazem na Lotyšsko a Estonsko. Analyzuje jejich společné soužití jak na základe politickoprávních, sociálních a ekonomických aspektu, tak na základe výzkumů, které byly v této souvislosti prováděny. Všechny výzkumy, ze kterých práce čerpá, se soustředily na hodnocení vzájemných vztahů Rusy i domácím obyvatelstvem a na to, jak svou současnou identitu vnímají sami Rusové. " Cílem práce je charakterizovat současný model soužití ruské menšiny a většinové společnosti naznačit možný vývoj v budoucnosti. Katedra občanské výchovy a filosofie Faculty of Education Pedagogická fakulta